Acute blood glucose responses on the second day of recovery from moderate vs. high intensity resistance exercise in women with type 2 diabetes - Carvalho da Cruz, Loumaíra; Teixeira-Araújo, Alfredo Anderson; Teixeira Passos de Andrade, Karoline; Kayola dos Santos Barros, Lorrana; Santos do Vale, Thamires; Souza Augusto, Sabrina; Rodrigues Moreira, Sergio (O Mundo da Saúde, 2022)
Resistance exercise (RE) can lower blood glucose in people with type 2 diabetes (T2D). However, greater clarity is needed regarding the RE intensity and time required for this acute response. Therefore, the aim of this study was to compare acute blood glucose responses on the second day of recovery from moderate vs. high-intensity RE in women with T2D. Twelve women with T2D (55.2 ± 4.0 years; 70.1 ± 11.4 kg; and 155.7 ± 3.3 cm) performed two experimental sessions seven days apart in a randomized order. For session 1: RE40% of one-repetition maximum test (1RM) and session 2: RE80%1RM, with 16 and 8 repetitions for each set, respectively, in 7 exercises with 3 circuits during 40min. Blood glucose was monitored for over 35h (first day: 24h and second day: 11h) every 5 minutes after each experimental session by the Continuous Glucose Monitoring System (Guardian REAL-Time model). Student’s t-test showed no significant difference in blood glucose on the second day (11h) after RE40%1RM vs. RE80%1RM sessions [respectively, 161.3 ± 62.3 mg.dL-1 vs. 157.2 ± 41.9 mg.dL-1; t (11) = 0.259; p = 0.800]. Two-way ANOVA for repeated measures showed that blood glucose responses every hour during recovery on the second day showed no significant differences between RE sessions [F (1.731, 19.039) = 0.688; p = 0.734]. We concluded that the acute blood glucose responses on the second day of moderate and high intensity RE did not differ among women with T2D.